Child Marriage in Indonesia: A Normative Analysis of Islamic Law and Nasional Marriage Law - Nur Asliah; Uswatun Hasanah; Sitinur Sadiyamue (PT. Ratu Bilqis Azzahira bekerjasama dengan Fakultas Syariah Universitas Islam Zainul Hasan Probolinggo, 2025)
This study examines child marriage in Indonesia from the perspective of Islamic law and national marriage law. The research aims to analyze the normative foundations of child marriage in Islamic jurisprudence and Indonesian positive law, as well as to assess their implementation in judicial decisions concerning marriage dispensation. This research employs a normative legal approach, relying on statutory regulations, classical and contemporary Islamic legal sources, and relevant court practices. The findings indicate that although Islamic law does not stipulate a specific minimum age for marriage, it emphasizes maturity and readiness, which align with the objectives of Islamic law to protect life, intellect, and lineage. In contrast, Indonesian national law, particularly after the enactment of Law Number 16 of 2019, establishes a strict minimum marriage age as part of child protection efforts. However, the practice of granting marriage dispensations by Religious Courts reveals a legal tension between normative regulations and social realities. This study argues that the persistence of child marriage reflects structural, cultural, and socio-economic factors that challenge both Islamic legal ideals and national legal frameworks. The research contributes to contemporary legal discourse by highlighting the need for a more integrative approach that strengthens child protection while remaining sensitive to Islamic legal principles and judicial practice in Indonesia.